Protection of children from sexual offences act and rules : and Sexual harassment of women at workplace (prevention, prohibition & redressal) act and rules, 2013 - Singh, Shiv Kinkar (Allabhad, 2014)
An Act to protect children from offences of sexual assault, sexual harassment nd pornography and provide for establishment of Special Courts for trial I such offences and for matters connected therewith or incidental thereto.
Keywords: Sexual harassment of women at workplace